The failure analyses on ZnO varistors used in high tension devices - Ramirez, M. A.; Bueno, Paulo Roberto [UNESP]; Ribeiro, W. C.; Varela, José Arana [UNESP]; Bonett, D. A.; Villa, J. M.; Marquez, M. A.; Rojo, C. R. (Springer, 2005)
The main purpose of this work is to evaluate the failure caused by electrical discharge on commercial ZnO varistor doped with oxide of Bi, Sb, Si, Cr, Co utilized in electric transmission systems. In order to observe the effect of electrical discharge over the microstructure and electrical properties of the varistors, two kinds of pulses were applied: long pulse (2000 ms) and short pulse (8/20 mu s). In both cases, a decrease in grain size and increase in micropores and leakage current were observed. The degraded samples present oxygen defficiency mainly in the grain boundary and phase tranformation from the bismuth oxide phase. (c) 2005 Springer Science+ Business Media, Inc.